Acquiring competencies for work in travel agencies: Formal and informal education in Serbia - Mišković Ivana (University Educons, Faculty of Sports and Tourism, Novi Sad, 2017)
Constant changes in the market and technological advancements condition swift outdating of knowledge and require staff that is open to changes, flexible, proactive, and adaptable. Human resources required by travel agencies must have the basic knowledge of economy, geography, catering, transportation, consumer psychology, and must know at least one additional foreign language. Considering the fact that quality of service in tourism mostly depends on the interaction of the service providers and guests, it is expected of the employees to always smile, be polite, empathic, attentive, and presentable. The process of education and preparation for employment in the agency sector in Serbia is conducted through a system of formal (3 levels of studies) and informal education, which entails taking expert courses in order to acquire licenses that are often necessary for the company to do business in accordance with professional standards and current laws. The aim of this paper is to analyse the current condition of both types of education, to question the sustainability of the currently used curriculum and the necessity of limiting the internship only to travel agencies and hotels, as is currently the case in most universities and colleges in our country. Furthermore, guidelines for innovating the process of practical education are provided in the paper for the purpose of a more quality and efficient realization of the schooling, and for the competencies of the candidates to be in accordance with the realistic needs of the labour market.